2018
DOI: 10.1080/14787210.2018.1425616
|View full text |Cite
|
Sign up to set email alerts
|

Non-prescription use of antibiotics among children in urban China: a cross-sectional survey of knowledge, attitudes, and practices

Abstract: There was a high proportion of primary caregivers self-medicate antibiotics for children in urban China, despite their insufficient knowledge about antibiotic use. Public health initiatives are needed such as public education campaigns and stricter government regulation of antibiotic use and availability in community pharmacies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 35 publications
8
61
1
1
Order By: Relevance
“…Despite equal proportions of parents in Zhejiang and Shaanxi choosing selfmedication or going to a doctor, results were significantly different on the subject of antibiotic use. Consistent with previous research [11], our study found that parents in the less developed Shaanxi province were more likely to keep antibiotics at home and to give their children antibiotics as SMA or prophylaxis. These findings mirror a study in Europe, which showed storing in-home antibiotics and self-medicating with antimicrobial drugs were more prevalent in less developed countries [32].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Despite equal proportions of parents in Zhejiang and Shaanxi choosing selfmedication or going to a doctor, results were significantly different on the subject of antibiotic use. Consistent with previous research [11], our study found that parents in the less developed Shaanxi province were more likely to keep antibiotics at home and to give their children antibiotics as SMA or prophylaxis. These findings mirror a study in Europe, which showed storing in-home antibiotics and self-medicating with antimicrobial drugs were more prevalent in less developed countries [32].…”
Section: Discussionsupporting
confidence: 91%
“…In China, previous studies have found regional disparities in parental understandings of and attitudes towards antibiotic use. Fewer caregivers in the less developed city of Xi'an recognized antibiotics as prescription drugs, while many more agreed that they could self-medicate their children with antibiotics for minor illnesses compared to their counterparts in the more developed city of Shanghai [11]. Also, it has been reported in Jiangxi, a less developed province in central China, that nearly 80% of parents believed antibiotics could cure viral infections, and about 50% thought antibiotics would help shorten the duration of upper respiratory tract infections [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations